1987
DOI: 10.1007/bf02555246
|View full text |Cite
|
Sign up to set email alerts
|

The effects of walking on the cross-sectional dimensions of the radius in postmenopausal women

Abstract: This report deals with the analysis of data from a 3-year clinical trial on the effect of walking on postmenopausal bone loss. Two hundred fifty-five women, with an average age of 57 at entry, were randomized into two groups, a walking and a control group. Bone measures in the shaft of the radius were carried out with a CT scanner in search of generalized skeletal effects rather than effects localized to the bones of the leg. Although bone density losses were comparable in the two randomized groups, changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 21 publications
0
36
0
2
Order By: Relevance
“…18 Even if the inverse association between finasteride and fracture risk is due to a decreased risk of falls, it is not clear if decreased risk of fracture represents a direct effect of androgen or an increase in estrogen levels due to increased levels of substrate for aromatase. And while previous studies of 5-␣ reductase inhibitors have not 20,21 Based on the inverse association observed in this study, these men may avoid 500 of these hip fractures, owing to the effects of 5-␣ reductase inhibition. In this study population, however, the use of these agents was fairly low, and the use of dutasteride almost nonexistent.…”
Section: Commentmentioning
confidence: 51%
“…18 Even if the inverse association between finasteride and fracture risk is due to a decreased risk of falls, it is not clear if decreased risk of fracture represents a direct effect of androgen or an increase in estrogen levels due to increased levels of substrate for aromatase. And while previous studies of 5-␣ reductase inhibitors have not 20,21 Based on the inverse association observed in this study, these men may avoid 500 of these hip fractures, owing to the effects of 5-␣ reductase inhibition. In this study population, however, the use of these agents was fairly low, and the use of dutasteride almost nonexistent.…”
Section: Commentmentioning
confidence: 51%
“…Therefore no overall treatment effects are calculated for the radius, although this is a bone site at risk for osteoporotic fractures, because only a few studies specifically loaded the radius [42,51,55]. In most studies the training of the forearms is only a small part of the training program, if at all, and is hardly reported [47][48][49][50]52,53,[56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of exercise and different levels of activity have been investigated successfully [14,15]. Children have been scanned at the forearm to verify bone mineral disorders [16,17] or to investigate age, sex and body size effects [18][19][20].…”
Section: Introductionmentioning
confidence: 99%